2010
DOI: 10.1177/0741932510383990
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Positive Behavior Support in School Settings

Abstract: This meta-analysis examined school-based intervention research based on functional behavioral assessment (FBA) to determine the effectiveness of key individualized positive behavior support (IPBS) practices in school settings. In all, 83 studies representing 145 participants were included in the meta-analysis. Intervention, maintenance, and generalization effects were measured by computing the percentage of nonoverlapping data points (PND). Overall, FBA-based interventions were found to be equally effective ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 87 publications
(51 reference statements)
9
83
0
6
Order By: Relevance
“…They simultaneously include withholding reinforcement for problem behavior, in essence combining differential reinforcement (Chowdhury and Benson 2011) and extinction (Iwata et al 1994) to maximize the effectiveness of functional consequences. Function-based interventions have been well documented in terms of their effectiveness across populations and settings (Gage et al 2012;Geiger et al 2010;Goh and Bambara 2010;Kliebert et al 2011;Newcomer and Lewis 2004). Functional consequences are often combined with other reinforcers to encourage desired as well as replacement behaviors (O'Neill et al 2014).…”
Section: Assessment Of Contexts and Functionsmentioning
confidence: 99%
“…They simultaneously include withholding reinforcement for problem behavior, in essence combining differential reinforcement (Chowdhury and Benson 2011) and extinction (Iwata et al 1994) to maximize the effectiveness of functional consequences. Function-based interventions have been well documented in terms of their effectiveness across populations and settings (Gage et al 2012;Geiger et al 2010;Goh and Bambara 2010;Kliebert et al 2011;Newcomer and Lewis 2004). Functional consequences are often combined with other reinforcers to encourage desired as well as replacement behaviors (O'Neill et al 2014).…”
Section: Assessment Of Contexts and Functionsmentioning
confidence: 99%
“…Meta-analyses have the following four purposes: (a) identification of variables that may have an influence on outcome variables, (b) summarizing the overall effectiveness of the treatment being examined, (c) describing the body of research as a whole, and (d) providing quantification for the effectiveness of an intervention (Blimling 1988;Busk and Serlin 1992;Busse, Kratochwill, and Elliot 1995). Three meta-analyses have investigated function-based interventions and therefore included studies utilizing FCT (Goh and Bambara 2010;Gresham et al 2003;Marquis et al 2000); they found that FBA-based interventions can produce positive behavioral changes. Further, one recent meta-analysis examined the use of augmentative and alternative communication (AAC), including via FCTbased interventions, to address challenging behavior (Walker and Snell 2013).…”
mentioning
confidence: 99%
“…This model describes strategies that are implemented with the whole school to improve behavior and school climate and to prevent or change patterns of problem behavior (17). Based on applied behavior analysis, personcentered planning (an approach designed to assist the individual in planning his or her life and supports, often to increase self-determination and independence), and inclusion principles, PBS aims to support behavioral success by implementing nonpunitive behavioral management techniques in a systematic and consistent manner (18, 19). PBS models of intervention seek to prevent problem behavior by altering conflictinducing situations before problems escalate while concurrently teaching appropriate alternative behaviors (8).…”
Section: School-based Behavioral Interventionsmentioning
confidence: 99%